Financial Self Efficacy, Financial Satisfaction, Financial Management Behavior, and Financial Well Being of Indonesian Women - Made Ayu Anggi Puspitadewi; Gede Sri Darma (Dinasti Publisher, 2025)
A woman must have good financial self-efficacy so that financial well-being can be achieved. The study was analysed financial self-efficacy, financial satisfaction, financial management behavior, and financial wellbeing of Indonesian women. The population in this study were all women aged 21-50 years and already working who were in the central region of Indonesia. Data analysis was carried out using the Partial Least Square (PLS) method using SmartPLS software version. The result of this study is financial literacy has a positive and significant effect on women's financial self-efficacy. Self-control has a positive and significant effect on women's financial self-efficacy. Money attitude has no effect on financial self-efficacy. Financial literacy has a positive and significant effect on women's financial satisfaction. Financial literacy has a positive and significant effect on women's financial management behavior. Financial self-efficacy has a positive and significant effect on women's financial management behavior. Money attitude has no effect on women's financial management behavior. Locus of control has a positive and significant effect on women's financial management behavior. Financial management behavior has a positive and significant effect on women's financial wellbeing. Financial self-efficacy mediates the effect of financial literacy on women's financial management behavior. Financial self-efficacy mediates the influence of self-control on women's financial management behavior. Financial self-efficacy is not able to mediate the effect of money attitude on women's financial management behavior.